Kemampuan Pemahaman Konsep Mahasiswa dalam Mengidentifikasi Penyelesaian Soal Integral Tak Tentu dan Tentu - Utari, Rahma Siska; Utami, Arini (Mathematics Education Journal, 2020)
One of basic skill that must be had by students before they solved a mathematics problem is conceptual understanding skills. This research aimed to describe the skill of students conceptual understanding in identification any problem at indefinite integral and definite integral. Problem identification was the first step they should did before they did next step to solve the problem. Research method used in this study was a descriptive qualitative research and about 30 students of 4th semester who took calculus integral course participating as the subjects. Test and interview were used as data collection techniques in this study. For next step data was reducted, presentated, and concluded using triangulation techniques. Based the result of this study known about 63,3% of students could be had to identification the answer of any integral calculus problem and they had good enough conceptual understanding skill. To identification the answer of any integral calculus problem students had been red and understood the basic concept of it and then they had been did a lot of practice of finishing various problem of it.